Cohesion in American political rhetoric: "the Gettysburgh Address", "I have a dream" and "Obama’s Inaugural Address" - Díez Prados, Mercedes; Cabrejas Eñuelas, Ana Belén (Estudios Ingleses de la Universidad Complutense, 2012)
The present study attempts to add to the existing body of literature on political rhetoric by analyzing in detail the cohesive devices used in three political texts - The Gettysburg Address, I have a dream and Obama’s Inaugural Address – and their potential persuasive function. We first carry out an analysis of cohesion in these three masterpieces of political writing, applying our own model based on the combination and adaptation of those found in Halliday & Hasan’s (1976) and Beaugrande & Dressler’s (1981), in order to cover a wider range of devices and, at the same time, ameliorate some flaws ascribed by critics to Halliday & Hasan’s (1976). The results reveal that, although they share similarities, the texts also showed differences in the cohesive devices employed. We then suggest a new dimension for the analysis of cohesion: what we have termed intertextual cohesion, a device to extend the scope of cohesion beyond the limits of the text. This tool has proved to be very effective to show the resonance of content and form among the three speeches analyzed.